The Aberrant Expression of MicroRNA-125a-5p/IGF2BP3 Axis in Advanced Gastric Cancer and Its Clinical Relevance. (7th April 2020) - Zhang, Jing; Ding, Fanghui; Jiao, Dan; Li, Qiaozhi; Ma, Hong
RNA-binding proteins have been associated with cancer development. The overexpression of a well-known RNA-binding protein, insulin-like growth factor 2 messenger RNA–binding protein 3, has been identified as an indicator of poor prognosis in patients with various types of cancer. Although gastric cancer is a relatively frequent and potentially fatal malignancy, the mechanism by which insulin-like growth factor 2 messenger RNA–binding protein 3 regulates the development of this cancer remains unclear. This study aimed to investigate the role and regulatory mechanism of insulin-like growth factor 2 messenger RNA–binding protein 3 in gastric cancer. An analysis of IGF2BP3 expression patterns reported in 4 public gastric cancer–related microarray data sets from the Gene Expression Omnibus and The Cancer Genome Atlas-Stomach Adenocarcinoma revealed strong expression of this gene in gastric cancer tissues. Insulin-like growth factor 2 messenger RNA–binding protein 3 expression in gastric cancer was further confirmed via quantitative reverse transcription polymerase chain reaction and immunohistochemistry, respectively, in an in-house gastric cancer cohort (n = 30), and the association of insulin-like growth factor 2 messenger RNA–binding protein 3 expression with clinical parameters and prognosis was analyzed. Notably, stronger IGF2BP3 expression significantly correlated with poor prognosis, and significant changes in insulin-like growth factor 2 messenger RNA–binding protein 3 expression were only confirmed in patients with advanced-stage gastric cancer in an independent cohort. The effects of insulin-like growth factor 2 messenger RNA–binding protein 3 on cell proliferation were confirmed through in vitro experiments involving the HGC-27 gastric cancer cell line. MicroR-125a-5p, a candidate microRNA that target on insulin-like growth factor 2 messenger RNA–binding protein 3, decreased in advanced-stage gastric cancer. Upregulation of microR-125a-5p inhibited insulin-like growth factor 2 messenger RNA–binding protein 3, and dual-luciferase report assay indicated that microR-125a-5p inhibited the translation of IGF2BP3 by directly targeting the 3′ untranslated region. These results indicate that the microR-125a-5p/insulin-like growth factor 2 messenger RNA–binding protein 3 axis contributes to the oncogenesis of advanced gastric cancer.